Strongly enhanced ferroelectric performance in Ca-doped barium titanate coatings produced by plasma electrolytic oxidation. Issue 10 (July 2019) - Chen, Xi; Wang, Linlin; Jia, Yanmin; Li, Yuliang; Li, Xiping; Dong, Weiping; Wang, Bin; Wang, Xiaoming
Abstract: In this study, Ca-doped BaTiO3 coatings were directly produced on a Ti substrate by a plasma electrolytic oxidation (PEO) process. Aqueous mixtures of 0.2 M Ba(OH)2 and different amount of CaO were used as electrolytes in the PEO process. The as-synthesized coatings were carefully characterized by different techniques and their ferroelectric performances were investigated. It is found that small amount of Ca doping is beneficial for the improvement of coatings' ferroelectric properties. The ferroelectric performance of the optimized Ca-doping coating is 350 times that of the undoped coating. However, excess Ca doping is harmful for the ferroelectric performances, which is due to the decreased amount of tetragonal phase and the formation of high-Ca compound. This study indicates that the ferroelectric properties of BaTiO3 coatings can be greatly improved by optimizing the doping amount of Ca. In addition, this study provides new insights of improving ferroelectric and piezoelectric properties of coating materials by chemical doping through the PEO technology.